Chitosan sponges and polycaprolactone nanoparticles carrying tranexamic acid as hemostatic agent: Synthesis, characterization and bioapplication. Issue 11 (15th September 2022) - dos Santos, Maria Carolina Fernandes; dos Santos Cavalcante, Luiza Peixoto; de Andrade, Karlivânia Ferreira; da Silva, Alan Frazão; de Araújo Ferreira Muniz, Isis; de Lima, Jefferson Muniz; Aguiar, Rebeca Tibau; Tavares, Josean Fechine; Castellano, Lúcio Roberto Cançado; da Silva, Sabrina Daniela; Bonan, Paulo Rogério Ferreti
Abstract: This study aimed to synthesize, characterize, and evaluate the hemagglutinating activity of chitosan sponges (Cs) and polycaprolactone nanoparticles transporting tranexamic acid. Sponges were prepared in various concentrations, lyophilized, and characterized by Fourier transform infrared spectroscopy, differential scanning calorimeter, thermogravimetric analysis, scanning electron microscopy, zeta potential, profilometry, and nuclear magnetic resonance ( 1 H NMR). Samples were evaluated for hemagglutinating potential and clotting time. The results confirmed the presence of the three components in the biomaterial, as well as stability in the oral environment since the loss of mass occurred only at high temperatures. Microscopy and profilometry demonstrated the samples' porosity. Hemagglutination was found to be complete in the Cs100PCL0, Cs75PCL25+TXA, Cs50PCL50+TXA, and Cs75PCL25 sponges, and those with chitosan in their composition presented reduced clotting times as compared to the control. The innovative Cs have stability, porosity, complete hemagglutination, and were able to significantly reduce clotting time.